2014
DOI: 10.1590/s1982-56762014000100004
|View full text |Cite
|
Sign up to set email alerts
|

Potential for using crude extract of Sarocladium oryzae for suppression of rice blast

Abstract: Crude extract of an isolate of the fungus Sarocladium oryzae (CNPAF So 20G), containing the antimicrobial cerulenin, was produced and its antagonistic potential on the rice blast pathogen Magnaporthe oryzae was asessed. Cerulenin was detected in crude extract of S. oryzae through thin layer chromatography showing a R f value of 0.63. The quantity of cerulenin in the crude extract was 237 µg.mL -1 . The in vitro inhibition of germination and appressorial formation of M. oryzae was assessed on an artificial hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Dozens of metabolites are known from Sarocladium/ Acremonium, including the antibiotic helvolic acid and antifungal cerulenin, produced by S. oryzae (Bills et al, 2004), and antimicrobial pyrrocidines A and B, produced by S. zeae (Wicklow et al, 2005). The putative protective action of S. zeae on maize ears against F. verticillioides and Aspergillus flavus was assigned to pyrrocidines, while a crude organic extract of a strain of S. oryzae, enriched in cerulenin content, was capable of reducing the severity of rice blast disease, caused by Pyricularia oryzae (Côrtes et al, 2014). Thirteen endophytic isolates were assigned to Ramichloridium sp., making it the second most abundant taxon isolated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Dozens of metabolites are known from Sarocladium/ Acremonium, including the antibiotic helvolic acid and antifungal cerulenin, produced by S. oryzae (Bills et al, 2004), and antimicrobial pyrrocidines A and B, produced by S. zeae (Wicklow et al, 2005). The putative protective action of S. zeae on maize ears against F. verticillioides and Aspergillus flavus was assigned to pyrrocidines, while a crude organic extract of a strain of S. oryzae, enriched in cerulenin content, was capable of reducing the severity of rice blast disease, caused by Pyricularia oryzae (Côrtes et al, 2014). Thirteen endophytic isolates were assigned to Ramichloridium sp., making it the second most abundant taxon isolated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…All the extracts studied by mass spectrometry have sugar adducts and are the major interference by ion suppression on presence of saccharides adducts derivatives, but the new extract has minor interferences, because it has less amounts of PDA. Côrtes et al (2014) also demonstrated that the S. oryzae crude extract inhibits the M. oryzae mycelial growth by 79 %, and Dethoup et al (2018) detected the inhibition of four rice pathogens (Alternaria padwickii, Bipolaris oryzae, Curvularia lunata and Fusarium moniliforme) using Talaromyces tratensis crude extract.…”
Section: Resultsmentioning
confidence: 91%
“…Rue extract effects on cell wall and plasma membrane of M. oryzae were assessed as described by Côrtes et al (2014), with rue extract at final concentrations of 3.04 and 5.07 ug uL -1 . The mixture of extract, conidia, and calcofluor white reagent was stored in the refrigerator for 24 hours, before examination under the microscope.…”
Section: Methodsmentioning
confidence: 99%